Cloud Point Extraction Coupled with Ultrasonic-assisted for Determination of Au and Ag in Water Samples by Flame Atomic Absorption Spectrometry - Li, Zonghao; Zhen, Wei; Tai, Zhigang; Yang, Yaling; Song, Jun; Lian, Yuanpei (Asian Journal of Chemistry, 2012)
A simple and practical preconcentration method was developed for the cloud point extraction of gold and silver. The method is based on the formation of hydrophobic complexes of gold and silver ions with sodium diethyldithiocarbamate (Na-DDTC) and Dow Corning DC-193 was added as a non-ionic surfactant. The phase diagrams of the binary system, water-surfactant (DC-193) and the ternary system, water-surfactant-fatty acids (nonanoic acid), were determined. Under the optimal conditions, the calibration curves were linear in the range of 10-500 μg/L and 10-800 μg/L with the detection limits of 3.4 μg/L and 2.7 μg/L for gold and silver, respectively. The enrichment factors are 25 and 20 for gold and silver, respectively. The relative standard deviations are 3.6 % for gold and 3.4 % for silver (n = 11). The method was successfully applied to the determination of gold and silver in water samples.